Research trends in occupational health and social responsibility: A bibliometric analysis - Bautista-Bernal, Irene; Quintana-García, Cristina; Marchante-Lara, Macarena (Elsevier, 2021)
Occupational Health & Safety (OHS) and Corporate Social Responsibility (CSR) are domains of research char- acterised by a great complexity due to their interdisciplinary nature. Although the interest in Occupational Health & Safety issues in the context of Corporate Social Responsibility has recently increased, more effort is needed to address the complexity of both research areas and to understand the dynamic and implications of their relationship. This research describes and analyses the state of the art in the literature and potential areas for further research regarding OHS and CSR. In total, 289 articles published between 1995 and 2018 related to both CSR and OHS were identified in the most reliable database, Web of Science Core Collection. The publications cover 932 authors, 142 journals, 53 countries or territories and 489 institutions, which include 313 universities in the entire world. We employ bibliometric methods to describe the evolution of publication activity, the most relevant contributors, the methodologies applied as well as the content of the articles in order to examine the main topics and research trends. Moreover, we explore the mapping of bibliographic coupling, co-word analysis of keywords and clusters analysis, which provides maps of knowledge based on data of bibliographic nature. Our study allows us to identify potential avenues for future research that could be meaningful to advance in the consolidation of CSR as an integral framework to support OHS.
Keywords: Salud pública; Responsabilidad social; Bibliometric analysis; Co-word analysis; Social Responsibility; Occupational Health & Safety; Sustainability; Safety management